Educación alimentaria y nutricional en el contexto educativo de los estudiantes de segundo año de la Escuela “José de San Martín” del cantón Ventanas, Provincia de Los Ríos - Bustamante Rubio, Johana Lisbeth (2019)
This research project presents a set of reflections on Food and Nutrition education in the Context of Education for Second Year of Basic Education, taking into account the need to promote activities that contribute to the improvement of students' academic performance, creating habits and providing adequate information on the correct use of food, making the most of the benefit to the physical and cognitive abilities of children. The school, in Initial and Primary Education, is the ideal means to carry out a food and nutrition education program. On the one hand because it is the medium that welcomes the entire population during the compulsory education stage. In school you can help acquire knowledge, habits and favorable attitudes in a gradual and systematic way. On the other hand, because the school welcomes children in the most important stage of their lives in which they are forming their personality and still have time to change and incorporate new health habits. At the same time, the teaching team, in addition to imparting the appropriate knowledge for each stage, can also contribute to the modification of behaviors and be a key part in the child's nutritional education